Penegakan Hukum Administrasi Terhadap Pengusaha Yang Tidak Membayar Upah Pekerja Yang Diskorsing Pada Proses Pemutusan Hubungan Kerja Dalam Penyelesaian Perselisihan Hubungan Industrial - Londa, Claria J; Pietersz, Jemmy Jefry; Soplantila, Ronny (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: Employers can take action to suspend workers/laborers who are in the process of being laid off by continuing to pay wages and other rights that workers/laborers usually receive.Purposes of the Research: To analyze the absence of supervision and the imposition of administrative sanctions, triggering the non-compliance of employers related to the obligation to pay workers' wages while suspended.Methods of the Research: The method used to analyze and discuss this problem is Normative Juridical. The problem studied in this research is regarding the government's authority to supervise and provide administrative sanctions to employers who do not pay wages for suspended workers.Results of the Research: The research results show that the government has the authority to carry out supervision and provide administrative sanctions to employers who do not pay the wages of suspended workers based on data from the Manpower Service and the results of supervision carried out by labor inspectors.